2007
DOI: 10.1074/jbc.m705369200
|View full text |Cite
|
Sign up to set email alerts
|

Endoplasmic Reticulum Chaperones Stabilize Nicotinic Receptor Subunits and Regulate Receptor Assembly

Abstract: We examined interactions between the endoplasmic reticulum (ER) chaperones calnexin (CN), ERp57, and immunological heavy chain-binding protein (BiP) and nicotinic acetylcholine receptor (nAChR) subunits. The three chaperones rapidly associate with newly synthesized nAChR subunits. Interactions between nAChR subunits and ERp57 occur via transient intermolecular disulfide bonds and do not require subunit N-linked glycosylation. The associations of ERp57 or CN with AChR subunits are long lived and prolong subunit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
42
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(43 citation statements)
references
References 48 publications
(66 reference statements)
1
42
0
Order By: Relevance
“…The calnexin and ERp57 ER-resident component of the biosynthetic machinery also form transient complexes with newly synthesized AChRs before full assembly occurs (17). The association of AChR subunits with ER proteins would decrease the rate of ERAD-dependent subunit degradation (17).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The calnexin and ERp57 ER-resident component of the biosynthetic machinery also form transient complexes with newly synthesized AChRs before full assembly occurs (17). The association of AChR subunits with ER proteins would decrease the rate of ERAD-dependent subunit degradation (17).…”
Section: Discussionmentioning
confidence: 99%
“…AChR subunits enter the ER cotranslationally in an unfolded state via the Sec61 translocon. Transient interactions with ER resident components of the biosynthetic machinery, such as BiP (13,14), calnexin (15,16), and ERp57 (17), then influence the folding process and protect immature subunits from degradation. Folding subunits are exposed to a variety of enzymes that catalyze posttranslational modifications (including glycosylation and palmitoylation) and regulate protein expression (18)(19)(20).…”
mentioning
confidence: 99%
“…Newly synthesized subunits interact with the general folding machinery including calnexin and BIP (16). In Caenorhabditis elegans, three genes are essential for functional reconstitution of the levamisole-sensitive AChR (L-AChR) (17).…”
Section: Discussionmentioning
confidence: 99%
“…In human cells, the chaperones in the ER, like CRT, ERP57 and BiP, associate with unassembled subunits or folding intermediates to regulate subunit stability, assembly and expression of receptor complex (Wanamaker and Green, 2007). The ER chaperones are involved in different biological processes with specific substrates to control the response to extracellular stimuli.…”
Section: Er Quality Control and Cell Signaling In Plantsmentioning
confidence: 99%
“…It is composed of 2α,β,γ and δ subunits. Evidence has shown that BiP, ERp57 and CNX associate with newly synthesized AchR subunits by stabilizing and sequestering them to regulate the level of assembled AchR in the ER (Wanamaker and Green, 2007). A conserved motif in the transmembrane domain of the subunits functions in the ER retention of the receptor.…”
Section: Er Quality Control Of Mutant and Unassembled Receptorsmentioning
confidence: 99%